Diagnostic performance of noninvasive fractional flow reserve derived from coronary computed tomography angiography in coronary artery disease: A systematic review and meta-analysis. (1st April 2015) - Deng, Song-Bai; Jing, Xiao-Dong; Wang, Jing; Huang, Chuan; Xia, Shuang; Du, Jian-Lin; Liu, Ya-Jie; She, Qiang
Abstract: Background: The study performed a meta-analysis of the diagnostic performance of fractional flow reserve (FFR) derived from coronary computed tomography angiography (FFRCT ) to assess the functional significance of coronary stenosis using FFR as the reference standard. Methods: We searched the electronic databases of PubMed, EMBASE, The Chorance Library, Medion and Web of Science for relevant articles published until August 2014. Pooled estimates of sensitivity, specificity, positive (LR +) and negative likelihood ratios (LR −) with the corresponding 95% confidence intervals (CIs) and the summary receiver operating characteristic curve (SROC) were determined. Results: Five studies, 706 patients and 1165 vessels or lesions were included in the meta-analysis. The pooled sensitivity and specificity for FFRCT at the per-patient level were 90% (95% CI, 85%–93%) and 72% (95% CI, 67%–76%), respectively. The corresponding pooled LR + and LR − were 3.70 (95% CI, 2.11–6.49) and 0.15 (95% CI, 0.11–0.22), respectively. The pooled sensitivity and specificity for FFRCT on the per-vessel or per-lesion basis were 83% (95% CI, 79%–87%) and 78% (95% CI, 75%–81%), respectively. Corresponding pooled LR + and LR − were 3.75 (95% CI, 2.09–6.74) and 0.22 (95% CI, 0.18–0.29), respectively. The area under the SROC (AUC) was 0.94 at the per-patient level and 0. 91 at the per-vessel or per-lesion level. Conclusions: The existing evidence suggests that noninvasive FFRCT has high diagnostic performance compared with invasively measured FFR for the detection of ischemia-causing stenosis in stable patients with suspected or known coronary artery disease (CAD).